2015
DOI: 10.1111/acer.12888
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Brief Screening Tool for Alcohol‐Related Neuropsychological Impairments

Abstract: This study indicates that the BEARNI is a useful screening tool in clinical settings for detecting ALs' motor and cognitive impairments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 46 publications
0
42
0
Order By: Relevance
“…Finally, two CSIs have recently been developed specifically for assessing alcohol-related cognitive impairments, the Brief Examination of Alcohol-Related Neuropsychological Impairments (BEARNI; Ritz et al, 2015) and the Test of Detection of Cognitive Impairment in Alcoholism (TEDCA; Jurado-Barba et al, 2017), though both have only been validated in AL populations not meeting ARCI diagnostic criteria (both CSIs can be accessed in the corresponding publications [the BEARNI is in French]). The BEARNI was designed as an easily administered CSI for assessing the deficits associated with alcoholism: working and episodic memory, visuospatial abilities, EF, and ataxia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, two CSIs have recently been developed specifically for assessing alcohol-related cognitive impairments, the Brief Examination of Alcohol-Related Neuropsychological Impairments (BEARNI; Ritz et al, 2015) and the Test of Detection of Cognitive Impairment in Alcoholism (TEDCA; Jurado-Barba et al, 2017), though both have only been validated in AL populations not meeting ARCI diagnostic criteria (both CSIs can be accessed in the corresponding publications [the BEARNI is in French]). The BEARNI was designed as an easily administered CSI for assessing the deficits associated with alcoholism: working and episodic memory, visuospatial abilities, EF, and ataxia.…”
Section: Discussionmentioning
confidence: 99%
“…The BEARNI was designed as an easily administered CSI for assessing the deficits associated with alcoholism: working and episodic memory, visuospatial abilities, EF, and ataxia. In its validation, Ritz et al (2015) found the BEARNI was considerably more sensitive when differentiating between ALs and controls (sensitivity = 98.4%) compared with the MMSE (9.5%) and Dementia Rating Scale (7.9%; Coblentz et al, 1973). However, the tool displayed relatively poor specificity (50%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These thresholds led to the establishment of operational criteria that can now be used in a clinical setting. If these findings are associated with a screening tool for alcohol-related neuropsychological impairments, such as the BEARNI [ 50 ], clinicians will be able to identify patients at risk of severe impairment and needing preventive action and specific care, including nutritional and hepatic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…They are lengthy to administer and often complicated; for example, in the study performed by Davies et al, administration lasted from 60 to 90 min [20], whilst Glass et al [21] used 6 different tests. A new test, the Bearni, has been recently proposed [22] but was not available at the time we began our investigation.…”
Section: Introductionmentioning
confidence: 99%